Characterization of carbapenem-resistant Acinetobacter baumannii isolates in a Chinese teaching hospital - Chang, Yaowen; Luan, Guangxin; Xu, Ying; Wang, Yanhong; Shen, Min; Zhang, Chi; Zheng, Wei; Huang, Jinwei; Yang, Jingni; Jia, Xu; Ling, Baodong (Frontiers in Microbiology, 2015)
Carbapenem-resistant Acinetobacter baumannii (CRAB) presents a serious therapeutic and infection control challenge. In this study, we investigated the epidemiological and molecular differences of CRAB, and the threatening factors for contributing to increased CRAB infections at a hospital in western China. 110 clinical isolates of A. baumannii, collected in last two years, were tested for carbapenem antibiotic susceptibility, followed by a molecular analysis of carbapenemase genes. Genetic relatedness of the isolates was characterised by multilocus sequence typing (MLST). 67 of the 110 isolates (60.9%) were resistant to carbapenem, 54 (80.60%, 54/67) of which carried the blaOXA-23 gene, most of them are classified as clone complex 92 (CC92). 77.62% of the 67 CRAB isolates were classified to CC92, and sequence type (ST) 92 was the most prevalent STs, followed by ST195, ST136, ST843 and ST75. One CRAB isolate of ST195 harbored plasmid pAB52 from a Chinese patient without travel history. The toxin-antitoxin elements of pAB52 related to adaptation for growth, which might have emerged as a common vehicle indirectly mediating the spread of OXA-23 in CRAB. Thus, CC92 A. baumannii carrying OXA-23 is a major drug resistant strain spreading in China. Our findings indicate that rational application of antibiotics is indispensable for avoiding widespread of drug resistance.